Lorenzo Market between Diversity and Mutation - David Frantz (Fondazione Eni Enrico Mattei (FEEM), 2003)
The aim of this paper is to investigate the relationship between the diversity of groups of workers and the local division of labour in the San Lorenzo Market, Florence, Italy. This empirical research may help distinguish the demographic, migratory and occupational patterns of the workers in accordance with their national origin. It shows that geographical origin is the key to the differences, specialisations and oppositions between the Florentines and the various groups of migrants on the one hand, and between these immigrant groups on the other hand. It shows too the mutation made by the conflict between global dynamics and a local labour market.
Keywords: Z10; 330; San Lorenzo Market; Immigrant workers; Diversity; Local division of labour; Migratory trajectories